Parafibromin is a nuclear protein with a functional monopartite nuclear localization signal. - Bradley, K; Bowl, MR; Williams, SE; Ahmad, B; Partridge, C; Patmanidi, A; Kennedy, A; Loh, N; Thakker, R (2007)
Parafibromin is a nuclear protein with a tumour suppressor role in the development of non-hereditary and hereditary parathyroid carcinomas, and the hyperparathyroidism-jaw tumour (HPT-JT) syndrome, which is associated with renal and uterine tumours. Nuclear localization signal(s), (NLS(s)), of the 61 kDa parafibromin remain to be defined. Utilization of computer-prediction programmes, identified five NLSs (three bipartite (BP) and two monopartite (MP)). To investigate their functionality, wild-type (WT) and mutant parafibromin constructs tagged with enhanced green fluorescent protein or cMyc were transiently expressed in COS-7 cells, or human embryonic kidney 293 (HEK293) cells, and their subcellular locations determined by confocal fluorescence microscopy. Western blot analyses of nuclear and cytoplasmic fractions from the transfected cells were also performed. WT parafibromin localized to the nucleus and deletions or mutations of the three predicted BP and one of the predicted MP NLSs did not affect this localization. In contrast, deletions or mutations of a MP NLS, at residues 136-139, resulted in loss of nuclear localization. Furthermore, the critical basic residues, KKXR, of this MP NLS were found to be evolutionarily conserved, and over 60% of all parafibromin mutations lead to a loss of this NLS. Thus, an important functional domain of parafibromin, consisting of an evolutionarily conserved MP NLS, has been identified.